“Renewable Energy Systems”: Role and Use of Parliamentary Technology Assessment - Manuel Baumann; Patrick Lichtner; Nuno Boavida; Camillo Fautz; Hanna Dura (Technikfolgenabschätzung - Theorie und Praxis, 2012)
The paper resumes the participation in PACITA (Parliaments and Civil Society in Technology Assessment) Summer School, in Liège, in June 2012
Keywords: O33; 300; Technology Assessment; Technology; Society; Innovation; Conference; PACITA; Technikbewertung; Society; Technology; Innovation